G03 An investigation on sex-based disparities in male and female collegiate athlete reactive strength index - Fletcher, Elliot (Graduate Journal of Sports Science, Coaching, Management, & Rehabilitation, 2024)
Reactive strength is the ability to effectively use a fast stretch shortening cycle (SSC) with the eccentric into a concentric contraction (Rebelo et al., 2022, Healthcare, 10, 593). A fast SSC is determined to be <200 ms due to a preliminary study by (Schmidtbleicher & Komi, 1992, Encyclopedia Sports Med. Vol. 3 Strength and Power in Sport) reviewing muscular contractions. Reactive strength is determined through two different metrics used within the literature which are ground contact time (GCT) and jump height (JH) allowing for understanding on how an athlete can utilise the myotatic reflex to react with the floor. Reactive Strength Index (RSI) is typically measured via drop jump (DJ) and 10/5 reactive pogo jumps. A novel way to measure RSI is via a rebound countermovement jump (RCMJ) which utilises RSI-Modified and includes time to take off instead of ground contact time. RSI is an important metric to measure because it has implications within sport-specific metrics like sprinting and jumping (Jarvis et al., 2022, Sports Med, 52, 301-330). However, some of the limitations of RSI are it is a ratio metric, and therefore RSI can mask underpinning metrics. As a result, additional metrics such as such a force, velocity and power can help better understand athlete development and the underpinning key performance indicators. However, many metrics within reactive jumps remain unsearched. Data will be collected from around 16 university athletes aged 18-25 currently competing in sport with at least one year’s experience in resistance training. Data will be collected using Hawkins dynamic force plates, sampling at 1000 Hz, and has recently been reported to be valid and reliable (Badby et al., 2023, Sports, 23, 4820) Participants will be asked to complete 3 DJ, RCMJ and 10/5 jump trials on two separate occasions separated by a minimum of 48 hours. Athletes will be instructed to perform a quiet standing period for 1 second before and after each jump to calculate body weight by the 5 × standard deviation method. Therefore, the study aims to compare the disparities between all three jumps aswell, sexes and the potential implications on performance. Previous studies displayed significant disparities between male and female participants. Therefore, the null hypothesis for this study is to display a non-significant difference across sexes aswell as between jumps. A limitation to this study is controlling the standardisation of variables such as squat depth during all tests.